Effect of a symmetric V‐shaped canyon on the seismic response of an adjacent building under oblique incident SH waves. (22nd February 2023) - Zhang, Ning; Lu, Haijun; Gao, Yufeng; Dai, Denghui; Zhang, Yu; Pak, Ronald Y.S.
Abstract: To elucidate whether an irregular topography affects the seismic response of nearby structures, an analytical solution to the dynamic interaction between a symmetric V‐shaped canyon and an adjacent building under the incidence of SH waves is proposed by using the wave function expansion method. The dynamic canyon‐soil‐structure interaction is decomposed into two problems of scattering and radiation. The building is idealized as a shear wall supported by a semicircular rigid foundation. The analytical solution can be degenerated theoretically to the canonical model of a shear wall embedded in a half‐space for either a zero depth‐to‐width ratio of the canyon or an infinite canyon‐building distance. Through a numerical comparison with two past exact solutions to the sole shear wall model as well as the sole V‐shaped canyon model, the correctness of the method in this paper is verified. A systematic parametrical analysis in both frequency and time domains is performed. It is found that the seismic response of the building may be amplified when it is on the wave‐facing side of the canyon. The degree of amplification is closely related to the size and depth‐to‐width ratio of canyon, the wave velocity of half‐space, and the incident angle and frequency content of seismic waves. The potential adverse effects of the V‐shaped canyon on the ground motion input of adjacent buildings should be considered in the seismic design.